2015
DOI: 10.1039/c5ra08958a
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of MTT and CCK-8 assay for evaluation of graphene cytotoxicity

Abstract: Cellular toxicity test is a key step in assessing the graphene toxicity for its biomedical applications. In this study, we investigated the cytotoxicity of graphene with 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2Htetrazolium bromide (MTT) and tetrazolium-8-[2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4disulfophenyl)-2H-tetrazolium] monosodium salt (CCK-8) assay on HepG2 cell line and Chang liver cell line. The cell viability data obtained by using MTT and CCK-8 assay showed inconsistent. Graphene induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…[39] The viability of rat aortic endothelial cells (RAECs) of all the groups after being exposed to different concentration of Tb 3+ -Alg-TCPP aqueous dispersion exceeds 95% except that at the highest concentration of Tb 3+ -Alg-TCPP aqueous dispersion (1:2) the biological activity was 80% (Figure 5). To further confirm the cytotoxicity of Tb 3+ -Alg-TCPP hydrogel materials, 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT) was performed to assay cell viability.…”
Section: Ph Sensorsmentioning
confidence: 96%
See 1 more Smart Citation
“…[39] The viability of rat aortic endothelial cells (RAECs) of all the groups after being exposed to different concentration of Tb 3+ -Alg-TCPP aqueous dispersion exceeds 95% except that at the highest concentration of Tb 3+ -Alg-TCPP aqueous dispersion (1:2) the biological activity was 80% (Figure 5). To further confirm the cytotoxicity of Tb 3+ -Alg-TCPP hydrogel materials, 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT) was performed to assay cell viability.…”
Section: Ph Sensorsmentioning
confidence: 96%
“…To further confirm the cytotoxicity of Tb 3+ -Alg-TCPP hydrogel materials, 3-(4,5-dimethylthiazol-2-yl)-2,5diphenyltetrazolium bromide (MTT) was performed to assay cell viability. [39] The viability of rat aortic endothelial cells (RAECs) of all the groups after being exposed to different concentration of Tb 3+ -Alg-TCPP aqueous dispersion exceeds 95% except that at the highest concentration of Tb 3+ -Alg-TCPP aqueous dispersion (1:2) the biological activity was 80% (Figure 5). The MTT results confirmed that Tb 3+ -Alg-TCPP hydrogels had almost no toxicity, showing good biocompatibility.…”
Section: Ph Sensorsmentioning
confidence: 96%
“…Jiao et al noted that CCK-8 molecules can be more significantly disturbed by graphene than by the MTT reagent. Additionally, optical properties of graphene may also result in the loss of light signals used for detection in assays in vitro [28].…”
Section: Nanoparticle Cytotoxicity Analyses and Their Limitationsmentioning
confidence: 99%
“…Apart from studying the cytotoxic effects of pnictogens nanosheets, we also investigated and compared the cytotoxicity with pnictogen(III) salts to generate a deeper understanding of the nanosheets′ relative toxicities. Lastly, control studies were carried out in cell‐free conditions to determine possible materials‐induced interferences between pnictogens and their salts with cell viability assay markers, that could in turn result in false results to be generated …”
Section: Introductionmentioning
confidence: 99%
“…Lastly,control studies were carriedo ut in cell-free conditions to determine possible materials-induced interferences between pnictogens and their salts with cell viability assay markers, that could in turn result in false results to be generated. [37][38][39]…”
Section: Introductionmentioning
confidence: 99%